The Wiley-Blackwell handbook of adulthood and aging - Whitbourne, Susan Krauss; Sliwinski, Martin J. (Blackwell handbooks of developmental psychology., 2012)
This exceptional collection draws on the most recent demographic data and combines classic research with cutting-edge approaches to provide an invaluable overview of the developmental psychology of the adult years. Covers a wide range of topics within adult development and aging, from theoretical perspectives to specific content areas. Includes newly commissioned essays from the top researchers in the field. Takes a biopsychosocial perspective, covering the biological, psychological and social changes that occur in adulthood.